Climate change and local medical systems: future availability of medicinal plants for the treatment of climate-sensitive diseases - Bem dos Santos, Eric; Paulino Albuquerque, Ulysses; de Lima Araújo, Elcida (Ethnobotany Research and Applications, 2026)
Background: Climate change has intensified the incidence of climate-sensitive diseases (CSD) while simultaneously altering the availability of medicinal plant resources, with potential consequences for human health and the functioning of local medical systems (LMS), particularly in semiarid regions. Methods: Species distribution models were developed for 83 woody medicinal plant species using occurrence records from GBIF and bioclimatic variables from WorldClim. Projections were generated for the year 2100 under current climatic conditions and three future scenarios (RCP 2.6, RCP 4.5, and RCP 8.5) to assess changes in the availability of medicinal resources used in the treatment of dengue, chikungunya, zika, malaria, leishmaniasis, and yellow fever. Results: Most species exhibited a contraction of suitable areas under future climate scenarios, with 68.7% showing consistent reductions across all projections. Losses were more pronounced among species associated with higher therapeutic diversity, and overall species richness declined markedly under the most extreme scenario (RCP 8.5). Conclusions: Projected climate change is likely to reduce the availability of medicinal plant resources in the semiarid region, increasing the vulnerability of local medical systems by limiting therapeutic options for the treatment of climate-sensitive diseases. Keywords: Arboviral diseases; Caatinga; Semiarid; Species distribution modeling